Drying characteristics of thin layer of potato (Solanum tuberosum): experimental and computational studies - Singh D.; Sengar M.; Patel S.K.; Kumar D.; Pal D.; Giri B.S.; Singh D. (My University, 2025)
Solar drying is a renewable energy-based technique which is widely used for food preservation purpose. In this study, various drying characteristics of the solar-dried Solanum tuberosum samples of different thicknesses have been investigated at variable climate condition of Lucknow. A mathematical model has also been developed to validate experimental results to predict the drying rate, free moisture content, and other parameters. Pre-treatment of the food samples was also done before the experimental runs on the fabricated solar dryer. Global radiation has also been monitored during the study to correlate the heat transfer rate in inner and outer sides of the solar drying chamber. SEM analysis has also been done to analyze the surface morphology of solar-dried samples. All solar dried food samples have uniformly heated. There was no hot-spot condition present on the surface of the samples. The drying efficiency and payback period of the fabricated solar dryer have also been calculated as 22.9% and 1.42 years, respectively. Model data have been found in good agreement with the experimental data within a 5% error. This modified model can be used for different agro-based food materials such as carrot, kiwifruit, and yam. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2023.